Pengaruh Cleanup Gasifier Terhadap Produk Gas Hasil Gasifikasi Menggunakan Media Geram Besi, Zeolit dan Serbuk Gergaji - Ariyanto, Putut, Nur Aklis, S.T., M.Eng (2017)
Cleanup gasifier is a device used to clean the gas product from gas contaminant and tar produced by gasification processes. Gasification is a process of change thermochemical solid fuel into gas, the necessary air is lower than the air used for combustion processes. This research was conducted to determine the effect of the cleanup gasifier using a variety of filter media (chip metal, zeolite and sawdust) from the product gas produced by gasification processes. The flame of the gas that has been cleaned is used for calculating the calorific value of boiling water. The research results showed that the use cleanup gasifier capable of cleaning gas product from gas contaminant and tar. The data obtained showed the highest flame temperature at 676° C using mixture of filter media, the best time effective flame for 72 minutes using chip metal of filter media, the fastest time of boiling water for 28 minutes using mixture of filter media, the highest value of sensible heat at 603,823 kJ using mixture of filter media, the highest value of latent heat at 1918,450 kJ using mixture of filter media.